2022
DOI: 10.2967/jnumed.122.264414
|View full text |Cite
|
Sign up to set email alerts
|

Fast and Accurate Amyloid Brain PET Quantification Without MRI Using Deep Neural Networks

Abstract: This paper proposes a novel method for the automatic quantification of amyloid positron emission tomography (PET) using the deep learning (DL)-based spatial normalization (SN) of PET images, which does not require magnetic resonance imaging (MRI) or computed tomography images of the same patient.The accuracy of the method was evaluated for three different amyloid PET radiotracers compared to MRIparcellation-based PET quantification using FreeSurfer. Methods:A deep neural network model used for the SN of amyloi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…The SUV at each voxel is standardized to the SUV of cerebellar gray matter to obtain the SUV ratio (SUVR). We used BTXBrain software (Brightonix Imaging, Republic of Korea) to measure SUVR in accordance with a previously described procedure …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The SUV at each voxel is standardized to the SUV of cerebellar gray matter to obtain the SUV ratio (SUVR). We used BTXBrain software (Brightonix Imaging, Republic of Korea) to measure SUVR in accordance with a previously described procedure …”
Section: Methodsmentioning
confidence: 99%
“…We used BTXBrain software (Brightonix Imaging, Republic of Korea) to measure SUVR in accordance with a previously described procedure. 37…”
Section: Brain β-Amyloid Analysismentioning
confidence: 99%
“…Therefore, the quantification results derived from the normalized image using predefined atlases remains accurate. While Kang et al have demonstrated the robustness of the BTXBrain through internal and external datasets [ 15 ], further investigations are warranted to validate its accuracy across diverse image sets and cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, MRI is not always available for all patients. Therefore, several approaches using artificial intelligence (AI) techniques have been proposed to achieve spatial normalization of brain PET images without the assistance of a matching MRI [ 5 , 14 , 15 ]. BTXBrain (Brightonix Imaging Inc., Seoul, Korea) software is a brain PET and single-photon emission computed tomography (SPECT) image quantification platform based on an AI-based fast and reliable spatial normalization algorithm.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, deep learning has been applied to predict quantitative values from amyloid PET images. Deep learning-based anatomical standardization method for 18 F-florbetaben or 18 F-flutemetamol PET without MRI has been proposed [12]. A deep learning model was developed to quantify SUVR from 18 F-florbetapir or 18 F-florbetaben PET images in a native space [13].…”
Section: Introductionmentioning
confidence: 99%